DEVELOPMENT OF PROBLEM – BASED LEARNING E – MODUL ON ADJUSTMENT JOURNAL MATERIAL IN VOCATIONAL HIGH SCHOOL STUDENTS - Balqis Syathiri (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The problem background of this research is the need forquality teaching materials and able to provide an understanding of adjustment journals in class X accounting. So that researchers develop E-based modules based on problem-based learning that have material suitability, attractiveness, ease of operation, and provide benefits that can make it easier for students to learn practically and effectively. There are 4 methods used in developing this e-module, namely identification, design, development, and dissemination. The instruments used are e-module validation sheets, student response questionnaires. The results showed an e-module validation questionnaire analysis developed from media experts of 4.5; Material experts at 4.6 and learning practitioners at 4.4, all three of which fall into the "very decent" category. The results of the practicality test of student responses in limited trials were 95% and field trials reached 96%, both of which were included in the "very practical" category. Based on the results, it can be concluded that e-PBL- based modules for adjustment journal material are feasible and practical to use in the accounting learning process